2020
DOI: 10.3389/fmicb.2020.00662
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Potential of Bdellovibrio and Like Organisms and Their Secreted Enzymes

Abstract: Bdellovibrio and like organisms (BALOs) are obligate predatory bacteria that selectively prey on a broad range of Gram-negative bacteria, including multidrug-resistant human pathogens. Due to their unique lifestyle, they have been long recognized as a potential therapeutic and biocontrol agent. Research on BALOs has rapidly grown over the recent decade, resulting in many publications concerning molecular details of bacterial predation as well as applications thereof in medicine and biotechnology. This review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 144 publications
(209 reference statements)
3
42
0
1
Order By: Relevance
“…Bdellovibrio and like organisms (BALOs) are a small group of bacteria that have the ability to target and prey on many Gram-negative bacterial species, such as Klebsiella, Escherichia, Acinetobacter, Salmonella, Pseudomonas, Aeromonas, Vibrio, Shigella , and Yersinia species (Dashiff et al, 2011 ; Duncan et al, 2019 ; Bratanis et al, 2020 ). The predation behavior of these organisms is a highly complex process: various prey are specifically recognized and killed, and the predator lives and replicates within the prey bacteria until all resources are exhausted (Lambert et al, 2009 ).…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bdellovibrio and like organisms (BALOs) are a small group of bacteria that have the ability to target and prey on many Gram-negative bacterial species, such as Klebsiella, Escherichia, Acinetobacter, Salmonella, Pseudomonas, Aeromonas, Vibrio, Shigella , and Yersinia species (Dashiff et al, 2011 ; Duncan et al, 2019 ; Bratanis et al, 2020 ). The predation behavior of these organisms is a highly complex process: various prey are specifically recognized and killed, and the predator lives and replicates within the prey bacteria until all resources are exhausted (Lambert et al, 2009 ).…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%
“…BALOs can inhibit biofilm formation and reduce preexisting biofilms of prey bacteria. Gram-positive bacterial biofilms induce an intracellular transcriptome response in B. bacteriovorus , leading to the secretion of several proteases, hydrolases, and nucleases, which is associated with the degradative effect of BALOs on Gram-positive bacterial biofilms (Im et al, 2018 ; Bratanis et al, 2020 ). in vivo animal models have demonstrated that predatory bacteria are nontoxic and nonimmunogenic in rodents (Russo et al, 2015 ), while in vitro predatory bacteria are nonpathogenic and nontoxic to several kinds of human cell lines (Gupta et al, 2016 ).…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%
“…In the context of fighting AR, predatory bacteria in nature contribute to limiting the spread of ARGs in different environments, because they can prey upon ARB and degrade their DNA [40] , [41] , reducing the ARG pools and their spread to other bacteria by HGT via conjugation or transformation [42] . Moreover, they can also limit the possibility of the transfer of ARGs via transduction by preying on bacteria targeted by phage-resistant bacteria [43] .…”
Section: Predatory Bacteria: What Are They? How Do They Kill?mentioning
confidence: 99%
“…1 , Supplementary Table 1 ), BALOs are also being explored as a feasible alternative to antibiotics as biocontrol agents in horticulture, aquaculture, livestock farming and food processing. In addition, they are being assayed for their application in other biotechnological processes such as waste water treatment, extraction of bioplastics, reduction of horizontal transfer of ARGs, and other environmentally-friendly applications in which the reduction of unwanted bacteria would be positive [43] , [85] , [130] , [131] , [132] ( Fig. 1 , Supplementary Table 1 ).…”
Section: Balos As Biocontrol Agentsmentioning
confidence: 99%
See 1 more Smart Citation